Biofertilizer application enhance chlorophyll content, membrane stability index, and anatomy of shallot (Allium cepa L.) leaves under drought stress - Azkiya, Nala; Siswanti, Dwi Umi (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2026)
Shallots (Allium cepa L.) are plants from the Amaryllidaceae family, Allioieae subfamily, and Allium genus. This perennial plant is estimated to have more than 1,000 species. Shallot leaves form a basal sheath. Biofertilizer contains rhizobacteria, which facilitate nutrient availability and uptake by plants. This research was conducted to determine the effect of biofertilizers on the physiological conditions and anatomical structure of shallot leaves (A. cepa L.) under drought-stress conditions. The treatments applied included the provision of biofertilizer and different drought stresses; biofertilizer was used with concentrations (10, 15, and 20 L/Ha), and the drought stress applied was 25, 50, and 75%. Data from measurements of chlorophyll a and chlorophyll b levels, Membrane Stability Index (MSI), stomatal density, leaf thickness, and metaxylem diameter were analyzed using SPSS 20, ANOVA test, DMRT with a confidence level of 95%. A biofertilizer concentration of 10 L/Ha is optimal for the Membrane Stability Index (MSI), a concentration of 15 L/Ha is optimal for chlorophyll a and b levels, leaf thickness, and metaxylem diameter, and a concentration of 20 L/Ha is optimal for increasing stomata density shallot leeks under drought stress conditions.